Analiza vojne na Hrvaškem - Tatalović, Siniša (Teorija in praksa, 1997)
The analysis of the war in Croatia was carried out from a strategic, organisational, political and actional viewpoint of both combating sides. The reason for this analysis was to help the international community in limiting or preventing such possible future occurrences by having the knowledge about the factors which trigger wars. As the battling sides in Croatia, Croatia and Serbia had very different political goals. Croatia strived for sovereignty andpolitical independence while Serbia acted towards establishing a state of (for) all Serbs. In view of military strategy, the Serbian side, uniting the Croatian Serbs, Yugoslav People's Armyand paramilitary voluntary formations from Serbia, used the strategy of combat of low and medium intensity, and in frame of that, the strategy of resistance which included three phases: latent and initial resistence, guerilla and manoeuvre combat. For quite a period of time, Croatia had no elaborated defence strategy, leaning towards a resolution of the crisis with as few victims as possible. The initial strategy of general defence later developed into a strategy of "stationed" defence with strict centralisation and professionalisation. The war ended with a total defeat of the Serb side after four years of more or less intensive armed conflict.
Keywords: vojna; war; Croatia; Hrvaška; Serbs; Srbi; vojaška strategija; vojaška agresija; mirovne sile